Application of Physics Model In Real-Time Bouncing Animation - Ngiik Hoon, Loh; Natasha, Rusdy Wong (ResearchTrentz, 2022)
This study investigates the application of physics algorithmic in achieving realistic time based animation. In order to produce realistic animation, the accuracy of timing adhering to the basic laws of physics is an extremely important to be included for the calculation. Based on the review, it would seem that creating realistic timing simulation in animation would be significantly difficult particularly in setting keyframes. It is often time consuming to setting the value frame by frame and estimating the correct timing to simulate a motion. Therefore, a case study of bouncing balls’ simulation is carried out with the application of physics formula, in order to produce a real time animation. Experiments have been carried out on different materials of the bouncing ball and different floor types. The results show that animation-based physics concept provides the animator the ability to control the realism of animation without setting the keyframe manually to achieve realistic-timing simulation.